2020
DOI: 10.1002/jmr.2880
|View full text |Cite
|
Sign up to set email alerts
|

The role of chlorine atom on the binding between acrylonitrile derivatives and fat mass and obesity‐associated protein

Abstract: In this work, seven acrylonitrile derivatives were selected as potential inhibitors of fat and obesity‐related proteins (FTO) by the aid of fluorescence spectroscopy, ultraviolet visible spectroscopy, molecular docking, and cytotoxicity methods. Results show that the interaction between 3‐amino‐2‐(4‐chlorophenyl)‐3‐phenylacrylonitrile (1a) and FTO was the strongest among these derivatives. Thermodynamic analysis and molecular modeling show that the main force between 1a and FTO is hydrophobic interaction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…CS1 and CS2 Attenuate LSC self-renewal, reprogram immune response by reducing LILRB4, sensitize leukemia cells to T-cell cytotoxicity, and show potent anti-leukemic efficacy in mouse models [136] acrylonitrile derivative 1a Binding FTO with chlorine atom, inhibits proliferation of leukemia cells [137] Saikosaponin D Inhibites AML cells proliferation, induce apoptosis and cell cycle arrest both in vitro and vivo, particularly in TKIs-resistant cells [138] let-7b-5p mimic Downregulate the expression of FTO and upregulate c-MYC level in AML line cells [139] ALKBH5 inhibitor Compound 1 and 2 Bioactive peptide Reduces leukemia cell viability inhibit AML cell proliferation and promote apoptosis in vitro, and reduce tumor growth in vivo [143,144] the clinical potentials of m6A regulators as diagnostic biomarkers and therapeutic targets. However, the underlying rationales still remain unclear and the clinical applications require further investigations.…”
Section: Rheinmentioning
confidence: 99%
See 2 more Smart Citations
“…CS1 and CS2 Attenuate LSC self-renewal, reprogram immune response by reducing LILRB4, sensitize leukemia cells to T-cell cytotoxicity, and show potent anti-leukemic efficacy in mouse models [136] acrylonitrile derivative 1a Binding FTO with chlorine atom, inhibits proliferation of leukemia cells [137] Saikosaponin D Inhibites AML cells proliferation, induce apoptosis and cell cycle arrest both in vitro and vivo, particularly in TKIs-resistant cells [138] let-7b-5p mimic Downregulate the expression of FTO and upregulate c-MYC level in AML line cells [139] ALKBH5 inhibitor Compound 1 and 2 Bioactive peptide Reduces leukemia cell viability inhibit AML cell proliferation and promote apoptosis in vitro, and reduce tumor growth in vivo [143,144] the clinical potentials of m6A regulators as diagnostic biomarkers and therapeutic targets. However, the underlying rationales still remain unclear and the clinical applications require further investigations.…”
Section: Rheinmentioning
confidence: 99%
“…Recently, Bai et al have screened several acrylonitrile derivatives as potential FTO inhibitors. And they found that chlorine atom was involved in the binding between these small molecules and FTO [ 137 ]. Saikosaponin D is identified as an FTO-targeted drug to impair AML cells proliferation, inducing apoptosis and cell cycle arrest both in vitro and vivo, particularly in TKIs-resistant cells [ 138 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation